A novel hybrid energy system combined with solar-road and soil-regenerator: Sensitivity analysis and optimization - Xiang, Bo; Cao, Xiaoling; Yuan, Yanping; Hasanuzzaman, Md.; Zeng, Chao; Ji, Yasheng; Sun, Liangliang (Elsevier, 2018)
To reduce the dependency of fossil fuels and greenhouse effect, the authors have proposed a novel solar-road and soil-regenerator hybrid energy system (SRSRHES), which utilizes a combination of Photovoltaic-Thermal (PVT) and soil heat storage technologies on the roadways. Design parameters and meteorological conditions affect the thermal storage performance of SRSRHES, which directly influences its annual performance and cost-effectiveness. Therefore, the study investigated the influence of flow rate, soil thermal properties, collector area, and borehole depth on electrical and thermal performance in three different cities with a numerical method to realize rational configuration of design parameters for the system. The results indicated that the recommended flow rates are 0.5, 0.3, and 0.3 kg/s in Beijing, Harbin, and Barkam respectively; Overall energy efficiency for different soils is different that is increased in the order of clay, sandy soil, sandstone, limestone, and granite. Collector area exerts a positive effect on total energy generation, but has a negative effect on overall energy efficiency. Borehole depth has a positive effect on both total energy generation and overall energy efficiency; Furthermore, the influence of various parameters on power generation performance is less than thermal storage performance, and overall energy efficiency mainly depend on thermal storage performance.